Congenital sensorineural deafness in Australian Cattle dogs in the UK: Prevalence and association with phenotype. (August 2021) - Marsh, O.; Freeman, J.; Pollard, D.; De Risio, L.
Highlights: 11.4% of Australian Cattle dog puppies had congenital sensorineural deafness. 9.7% puppies were unilaterally affected and 1.7% were bilaterally affected. Dogs with a face mask were at reduced risk of congenital sensorineural deafness. Abstract: The Australian Cattle dog (ACD) is one of many breeds predisposed to congenital sensorineural deafness (CSD). The objective of this study was to estimate CSD prevalence and investigate any association with phenotype in the ACD in the UK. The database of the authors' institution was searched for ACD puppies undergoing brainstem auditory evoked response (BAER) testing for CSD screening (1999–2019). Inclusion criteria were BAER performed at 4–10 weeks of age, testing of complete litters and available phenotypic data. The age, sex, coat and iris colour, presence and location of face and body patches, hearing status and BAER- determined parental hearing status of each puppy were recorded. A multivariable mixed-effects logistic regression model was used to calculate odds ratios and 95% confidence intervals to determine whether any of these variables were significantly associated with CSD, while adjusting for clustering at litter level. Inclusion criteria were met for 524 puppies. Hearing was bilaterally normal in 464 puppies (88.6%). The prevalence of unilateral and bilateral CSD was 9.7% and 1.7%, respectively. On the basis of multivariable analysis, the presence of a pigmented face patch was the only phenotypic variable significantly associated with CSD, and was linked to a reduced risk of the condition. The prevalence was similar to that reported in an Australian population of ACDs. The key findings from this study were that overall CSD prevalence in the ACD population in the UK was 11.4%, and puppies with a face patch were at reduced risk of the condition.